PENGARUH METODE PEER TUTORING BERBANTUAN MEDIA ALAT PERAGA SEDERHANA TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 1 PARIGI TENGAH - Apriyani, Putri Musdalifa; Ali, Muhammad (Universitas Tadulako, 2021)
This study was conducted to determine whether there was an influence of the Peer Tutoring Learning Method Assisted by Simple Teaching Aids on the Learning Outcomes of Class X Students of SMA Negeri 1 Parigi Tengah. This research was a quasi-experimental design with the non-equivalent pretest-posttest design. The population of this study were all students of class X MIPA SMA Negeri 1 Parigi Tengah. The sampling technique used in this study was proposive sampling with the research sample being class X MIPA 1 (n=22) as the experimental group and class X MIPA 2 (n=19) as the control group. The instrument used was a test of learning outcomes in the form of multiple-choice questions that have been validated and tested. Based on the results of data processing, the average posttest score for the experimental class was 15.90 and the control class was 11.31. Data analysis was carried out using a two-party t-test statistical technique. The results of the analysis obtained the value of tcount = 5.59. The value of ttable = t(0.05)(39) = 2.04 at the level of significance = 0.05 and dk = 39. This means, tcount value was outside reception area H0 so that H1 was accepted. It can be concluded that there was an effect of peer tutoring learning methods assisted by simple teaching aids on the learning outcomes of class X students of SMA Negeri 1 Parigi Tengah.